Menara Persekutuan Melaka / Muhammad Taqiyuddin Iqbal ... [et al.] - Muhammad Taqiyuddin, Iqbal; Mior Muhammad, Adamlullait; Norbatrisyia, Norhaizat; Nuryasmin Fikriyah, Zainal (2019)
Menara Persekutuan Melaka is located at Jalan Persekutuan, Hang Tuah Jaya, 75450 Ayer Keroh Melaka which it is in the middle of MITC Melaka. Menara Persekutuan Melaka is a government building and it is built for government agencies at Melaka. The total occupant of the building is 781 people and the total department in the building is 27 departments including, PERHILITAN, Arkib Negara Malaysia Melaka, Jabatan Perancangan Bandar Dan Desa and more. The facility that provided in this building is toilets, cafeteria, prayer rooms and parking lots around the building. For the building services, there are 7 types of services in the building such as water supply system, firefighting system, lift system, air conditioning system, electrical distribution system, security system and telecommunication system. In maintenance management, it explains about the organizational objectives. The objective is the organization aim to grasp the achievement, a systematic structure of organizational makes the employee easier to work better, it also allows it to remain delivering excellence in every works within the organization, and every position needs to understand their role in a building’s operation maintenance to do their work better. The organization chart is including the facility manager in the building, assistant manager, electrical facility and more. There is also the responsible for every role in the building. Planning is a key element of maintenance management. The execution of maintenance plans need to be monitored to ensure that the actual outcomes match the expected outcomes. If there is no maintenance planning, policy, and programme in the building will face many problems such as delays and lost time during the completing of jobs, incorrect identification of materials resulting in false starts, delays or makeshift repairs and also poor co-ordination of personnel resulting in excessing waiting and idle time. For the Menara Persekutuan Melaka, they have their maintenance planning with the suitable seclude. So they have their guideline for the maintenance work. So the life span by the Menara Persekutuan Melaka can be increase and the aesthetic value of the building can be remained for a long term. For chapter building design and technology provide and explain about the building design and concept by architect. This building use a specific shape as in geometrical shapes with the identity of Melaka that located at the roof of Menara Persekutuan Melaka. For services and facilities, this chapter explain about all the services in the whole building which is are all the item in Menara Persekutuan Melaka such as sewerage systems, mechanical and electrical system, firefighting system, security system and telecommunication system. Besides, this chapter also explains about the special technologies that are being used such as Computerized Maintenance Management System (CMMS) and Building Automation System (BAS). Other than that, these technologies also help this building towards a well-planned maintenance management system as well as towards a better building. Next, for the building condition assessment, we have summarise that the importance of finding defects to maintain and keep the building in a good condition, looks aesthetic and prestige also keep it functionality and performance. For Menara Persekutuan Melaka, the building on good condition and less of defect. Ambang Wira have their schedule to make sure the inspection work going smoothly the building surveyor need to follow the procedure step by step. The proper maintenance and inspection of building by Ambang Wira make the building less defect because many defect that happen at the building they take fast action to solve the problem. Menara Persekutuan Melaka do not have benchmarking process, key performance indicator (KPI) and penalty or deduction for the maintenance management. They only use minor broke down for a day repairing and the major broke down with suitable time or day to finish repairing. By the way, their maintenance strategy or preventive plan maintenance that we take for this chapter is suitable for this chapter because it is the strategy that Ambang Wira use as strategy to maintain the building. Maintenance stratergy is a long-term that covering all aspects of maintenance management which sets the direction for maintenance management and contain firm action plans for archiving a desired future state for maintenance function. The plan preventive maintenance that Ambang Wira use very suitable because the outcome from their plan preventive maintenance, there are less of breakdown or defect at the building. The legal aspect for this chapter is tenancy agreement, building service contract, and law regulation related to the building such Uniform Building by Law 1984, Act 133, Street Drainage and Building 1974, Occupation Safety and Health 1994 and Electrical Supply Act 1990. For Menara Persekutuan Melaka, they do not have tenancy agreement between the agency or office because all the agency is government agency. The building was built for all agency at the building have their office at Melaka. Tenancy only have between cafeteria and the owner of the building. For service contract, the agreement between services provided at the building with the owner. For laws and regulation, the building was complying with the act that provided to the building. All laws that we check such UBBL, Street, drainage and building Act, OSHA and Electrical Supply Act are complying at the building. So the building is safety and suitable with the occupant because of the comply with the act and regulation. Last but not least, in chapter Financial and Maintenance Management, it explains about Menara Persekutuan Melaka has their financial management to maintain the building in a good condition. Ambang Wira is acompany that responsible to manage the whole building and get the financial income from JKR to manage and to expand the life period of the building with a good maintenance work. On 2018, the budget that they get for the maintenance and the whole utilities is RM 1,800,800.00. From that money, they use for the expenditure such as general expenditure, utilities, maintenance, civil and structure, and the others. It also has some maintenance that have not be paid every month such as sewerage and the permit of the lift. So the maintenance department, Ambang Wira will have their schedule for the maintenance budget. For the total expenditure of the building on 2018 is RM108,991.18. Next, the forecast 2019,2020 and 2021 the budget for the maintenance gain remain especially for 2020 and 2021 because the increases of the salary of maintenance department.